Adsorption of Congo Red (Acid Red 28) Azodye on Biosynthesized Copper Oxide Nanoparticles - Batool, Madiha; Qureshi, Muhammad Zahid; Hashmi, Farwa; Mehboob, Nida; Daoush, Walid M. (Asian Journal of Chemistry, 2019)
A green synthesis of copper oxide nanoparticles and its removal efficiency of azodye were studied. Biosynthesis of stable copper oxide nanoparticles were preformed using Aloe barbadensis leaf extract as a size and shape-directing agent for preparing of spherical copper oxide nanoparticles by calcination at 400 °C. The leaf extract of Aloe barbadensis was prepared in deionized water. The produced copper particles were calcined at 400 °C to produce copper oxide nanoparticles. The characterization of copper oxide nanoparticles was performed by XRD, SEM, FTIR, UV spectroscopy. The XRD analysis showed that the average particle size was between 5-30 nm. The shape of the copper oxide nanoparticles was spherical and cubic. EDX of the synthesized nanoparticles showed the composition consists of 68 % copper. The UV-visible spectrum analysis confirms an absorption peak at 200-400 nm of the produced CuO nanoparticles. The FTIR analysis of the copper oxide particles indicate the presence of the organometallic Cu-O bond between Cu and O. The obtained copper oxide was used as a removing agent of Congo red dye. The effect of variables like concentration, time, pH, adsorbent dosage were studied. It was observed from the results that the maximum dye removal occurs at pH of 4, the concentration of nanoparticles was 1 mg/L and the maximum time for dye removal was 120 min. The Langmuir isotherm model was calculated to study the adsorption efficiency of the Congo red dye on the produced copper oxide nanoparticles. The kinetics of pseudo second order is followed by adsorption. The calculated sum of square was 0.012 and r2 = 0.98. it was observed that the model fit the best and straight line with r2 value of 0.991 and probability value of 1.6E-5. The nanoparticles remove 70 % of the Congo red dye from its solution. This showed that the copper oxide nanoparticles has efficient capacity of azodye degradation.